2019
DOI: 10.1039/c8sm02616e
|View full text |Cite
|
Sign up to set email alerts
|

Quadruplex knots as network nodes: nano-partitioning of guanosine derivates in supramolecular hydrogels

Abstract: Gua/GMP hydrogels are formed by disordered microcoils of intertwined filaments (knots, rich in gua) connected by long linear GMP-rich threads. Gua provides flexibility and thread attraction, responsible for hydrogel stability (AFM image is 2.5 × 2.5 μm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…As a result of its high aqueous solubility, GMP alone does not form a gel at neutral pH. However, upon addition of phosphatefree guanosines, gelation occurs and the modulation of the GMP/guanosine ratio can be used to finetune the resulting material properties 106,107 .…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…As a result of its high aqueous solubility, GMP alone does not form a gel at neutral pH. However, upon addition of phosphatefree guanosines, gelation occurs and the modulation of the GMP/guanosine ratio can be used to finetune the resulting material properties 106,107 .…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…G4 systems generate fibrous networks capable of entrapping large amounts of water, which allows the formation of self-supporting hydrogels. Since Gellert et al detailed that 5-GMP could generate self-assembled hydrogels in 1962, considerable advances have been made in the formation of stable Guo-based hydrogels due to their biological significance. , However, two disadvantages cannot be ignored: the low lifetime stability and the need for excess cations. Thus, their use in many applications is currently hindered, but different strategies have been developed in recent years to enhance the properties of these hydrogels for biological purposes, especially for tissue engineering. ,, Importantly, because of the additional H-bonding edges and its ability to create π–π stacks, guanine has the highest self-assembly capability of the five nucleobases.…”
Section: Nucleoside-based Supramolecular Hydrogelsmentioning
confidence: 99%
“…Knots and links may also occur between more than two components of DNA. For example, a recent work demonstrated that knots and links between four-helices of DNA (that were made by self-assembled G-quadruplexes formed by GMP and Guanosine) can be attributed to the formation of highly hydrated gels [ 11 ].…”
Section: Introductionmentioning
confidence: 99%